On the significance of the documents of the State Archives of the Republic of Crimea in understanding the historical lessons of the First World War - A. V. Ishin (Проблемы постсоветского пространства, 2017)
In the article published two unknown ranee arcival document, allowing newly to give a glance on the geopolitical context of the finishing stage of First world war, coinciding in Russia with a period between February and October revolutions.